Four new species of the genus Hexarhopalus Fairmaire, 1891 (Coleoptera, Tenebrionidae, Stenochiinae) from Vietnam and India - Purchart, Luboš (Zootaxa, 2025)
Three new species of the genus Hexarhopalus—H. (Hexarhopalus) kaminskii sp. nov., H. (Hexarhopalus) ruzzieri sp. nov. and H. (Leprocaulus) kontumensis sp. nov. from Vietnam and one new species—H. (Leprocaulus) arunachalpradeshensis sp. nov. from India are described. First additional specimens of H. masumotoi Bečvář & Purchart, 2008, H. lilligi Bečvář & Purchart, 2008 and H. sinjaevi Bečvář & Purchart, 2008 are reported since their description based on a single or two type specimens, respectively. H. lilligi is reported as new for Laos. A lectotype is designated for Derosphaerus binhanus Pic, 1922. The latter species is redescribed and transferred to the genus Hexarhopalus as H. binhanus (Pic, 1922) comb. nov. and reported as new for Thailand and Laos. An updated checklist of all known Hexarhopalus species is provided.